Overcoming stalled translation in human mitochondria - Wesolowska, Maria T.; Richter-Dennerlein, Ricarda; Lightowlers, Robert N.; Chrzanowska-Lightowlers, Zofia M. A. (Frontiers in Microbiology, 2014)
Protein synthesis is central to life and maintaining a highly accurate and efficient mechanism is essential. What happens when a synthesising ribosome stalls on a messenger RNA ? Many highly intricate processes have been documented in the cytosol of numerous species, but how does organellar protein synthesis resolve this stalling issue ? Mammalian mitochondria synthesise just thirteen highly hydrophobic polypeptides. These proteins are all integral components of the machinery that couples oxidative phosphorylation. Consequently, it is essential that stalled mitochondrial ribosomes can be efficiently recycled. To date, there is no evidence to support any particular molecular mechanism to resolve this problem. However, here we discuss the observation that there are four predicted members of the mitochondrial translation release factor family and that only one member, mtRF1a, is necessary to terminate the translation of all thirteen open reading frames in the mitochondrion. Could the other members be involved in the process of recycling stalled mitochondrial ribosomes ?